Dynamics of Tradition : Islamic Theology and Law in Relation - Nassery, Idris,; Tatari, Muna, (Middle East and Islamic Studies E-Books Online, Collection 2026., 2026)
This book invites the reader to explore how Islamic theology and law have shaped, challenged, and inspired each other across centuries. What does it mean, for example, when a legal rule embodies theological debates on divine justice? We unpack questions like this by diving into the rich history and modern-day relevance of theology and legal theory in Islam, using rare manuscripts and new historical findings. The book's contributors offer fresh perspectives on how Islamic scholars tackled pressing social issues and adapted their thought to evolving contexts. This work stands out for its engaging examination of Islam's intellectual legacy and its potential pathways for today. Contributors are Mohammed Abdelrahem, Ahmad Atif Ahmad, Maha El-Kaisy, Mohammed Fadel, Ramon Harvey, Serdar Kurnaz, Abdul Rahman Mustafa, Najah Nadi and David Vishanoff.